Effect of organic matter and sulfur in the availabilityof phosphorus in different soil texture in Basrah Governorate - م.م. وفاء عبد الامير احمد ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
A laboratory experiment was conducted to study the effect of adding organic matter and sulfur on the dissolved and available phosphorus in two soils first, a clay loam from Abu al-Khasib and the second loamy sand, from Barjisia. Three levels of superphosphate fertilizer are zero, 0.03 and 0.06 g P2O5 kg -1 soil, three levels of organic fertilizer are zero, 25 and 50 g organic matter kg - 1 soil and two levels of sulfur are zero and 50 g sulfur kg -1soil.